Examining the Efficacy of Inquiry-based Approaches to Education - Scott, David M; Smith, Cameron; Chu, Man-Wai; Friesen, Sharon (Alberta Journal of Educational Research, 2018)
Educational jurisdictions around the world have introduced curricular initiatives that emphasize the need for students to engage in inquiry-based education. This shift, has been met by significant public opposition, particularly in the Canadian context. Results from this study indicate that criticisms of inquiry-based approaches to education are largely directed at discovery learning, which has limited educational value. We note the significant affordances of guided forms of inquiry, such as problem-based learning, and approaches to inquiry aligned with the authentic education movement. Additionally, we highlight the specific instructional supports needed for processes of inquiry to promote elements, such as critical thinking skills and flexible problem solving abilities, necessary for success in a rapidly changing world.